Pengaruh Keaktifan Komunitas Belajar Terhadap Kompetensi Profesional Guru SMP di Kecamatan Ngawen Kabupaten Blora - Sri Maya Harum Krisstiyaningsih; Bunyamin Bunyamin; Muhammad Prayito (Universitas Negeri Malang, 2026)
Abstract: Teachers' professional competence is a key factor in realizing adaptive and innovative learning. However, the 2025 Education Report data indicates that the quality of learning in Blora Regency's junior high schools is at a moderate level and tends to decline, partly due to suboptimal learning community activities. This study aims to analyze the influence of learning community activities on the professional competence of junior high school teachers in Ngawen District, Blora Regency. The study employed a quantitative approach with an ex post facto design and a correlational research model. The population consisted of 162 teachers, with a sample of 118 teachers selected using proportional random sampling. Data were collected using a Likert-scale questionnaire (1–4) that had been tested for validity and reliability, with Cronbach's Alpha coefficients of 0.91 for the learning community activities variable and 0.93 for teacher professional competence. Data analysis was conducted using descriptive and inferential statistics, including simple linear regression with SPSS. The results revealed that learning community activities have a positive and significant effect on teacher professional competence, as indicated by a regression coefficient of 0.643 and a significance value of 0.000 (